PENYELESAIAN HUKUM KEADILAN RESTORATIF TERHADAP PELAKU PENGANIAYAAN - Nofarizal, Dedi; Yusuf, Yusuf; Pardede, Rudi (LPPM STIH Awang Long, 2024)
The issues above are rooted in the focus on a criminal act and the justice achieved through resolving a criminal case. The perspective on the meaning of a crime and punishment adopted in the current traditional criminal justice system is that “a crime is a violation of the state, defined by lawbreaking and guilt,” which is rigid and does not allow freedom for victims and perpetrators to resolve their cases. Based on research findings, it is known that the implementation of restorative justice for perpetrators of assault in the jurisdiction of Dumai Police, based on the Regulation of the Indonesian National Police Number 8 of 2021 concerning the Handling of Criminal Acts Based on Restorative Justice, has not been running effectively. Many cases between victims and perpetrators have not reached an agreement, making the process only viable if both parties, the victim and the perpetrator, agree to resolve the issue through restorative justice. The obstacles include the influence of third parties from the victim's family on the victim, the involvement of interested parties in the matter, the lack of understanding of restorative justice among the community, and communication barriers between the perpetrator and the victim. Efforts to overcome these obstacles involve providing input to victims and perpetrators regarding the issue, preventing interference from uninterested parties, increasing public understanding of restorative justice, and improving communication between the perpetrator and the victim.